Study of the thermal resistance of alpha-phase aluminum oxide (alpha-Al2O3) films deposited on the paper substrate - Lisboa, A. J. T.; Vasconcelos, N. S. L. S.; Rangel, J. H. G.; Oliveira, M. M. O.; Longo, E. [UNESP]; Varela, J. A. [UNESP]; Vasconcelos, J. S. (Elsevier B.V., 2014)
The purpose of this study was to increase the thermal resistance of a cellulose substrate, using films (a mixture of corundum-phase aluminum oxide, (x-Al2O3, and a PVA solution). The corundum phase, which was chosen due to its high thermal resistance, was obtained using an adaptation of Pechini's polymeric precursor method. A polyvinyl alcohol (PVA) solution was used as a medium for mixing the oxide for subsequent deposition on a paper substrate. The materials were characterized by X-ray diffraction (XRD) and field emission gun scanning electron microscopy (BEG-SEM) coupled with energy dispersive X-ray spectrometry (EDS). The thermal behavior of the material was investigated by thermogravimetry (TG) and differential scanning calorimetry (DSC). The EDS results indicate that all the samples with deposited a-phase aluminum oxide contain the chemical elements (Al and O) originating from the a-phase, while the surface analysis indicated that the paper substrates were completely coated with the films. The TG and DSC analyses of the thermal resistance of the film-coated substrate indicate that it was impossible to increase the thermal resistance of the paper substrate because the events that occurred (decomposition of cellulose and pyrolysis of lignin, hemicellulose and PVA) took place in the same temperature range, as has been reported in the literature for samples of the paper substrate without deposited film. (c) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Films; Corundum; Thermal resistance